Continental philosophy - Kononovich, Lila; Garcia, Pablo; Films for the Humanities & Sciences (New Jersey : Film For The Humanities & Sciences, 2004)
This program delves deeply into concepts and thought processes that fueled the inquiries of the era's major exponents: Hegel's dialectic, Marx's dialectical materialism, Kierkegaard's lone individual standing before God, Nietzsche's declaration that God is dead, Husserl's intentionality, Heidegger's Dasein, and Sartre's assertion that people are condemned to be free. Illuminating commentary is offered by Merold Westphal, of Fordham University, and Alexander Nehamas, of Princeton University. Excerpts from Hegel's Philosophy of Right, Nietzsche's Thus Spoke Zarathustra, and Heidegger's Being and Time are included
Title from title screen
Executive producers, Chris Scherer, Camila O'Donnell
DVD format
Keywords: Philosophy; Philosophy -- Modern -- 19th century; Philosophy -- Modern -- 20th century; Philosophy, European -- 19th century; Philosophy, European -- 20th century